Incidence of Transitional Period Reproductive Disorders in Crossbred Cows - Sachin; Sharma, Amit Kumar; Ahuja, Ankit; Thakur , Depika; Kumar, Pravesh; Sharma, Akshay; Sood , Pankaj (The Indian Journal of Animal Reproduction, 2024)
The present study was conducted to record the transitional period reproductive disorders in crossbred cows. A total of two hundred seventy eight (N=278) crossbred cows with different parities were studied to record the incidence of reproductive disorders viz., dystocia, metritis, genital prolapse and retained fetal membranes. Overall incidence of transitional period reproductive disorder recorded in current study was 34.9% with highest incidence in dystocia (16.7%) followed by metritis (11.7%), genital prolapse (3.7%) and retained fetal membrane (2.7%), respectively. Adult animals (<7 yrs, 65.9%) were more susceptible for reproductive disorders than older cows (> 7yrs, 34.1%; P<0.05). Majority (93.8%) of the affected animals had prolonged postpartum anoestrus and lower conception rates. In conclusion, one-third of the crossbred cows are affected with transitional period reproductive disorders. Therefore, there is a dire need to prevent reproductive disorders through appropriate management of cows.